Reasonable decision of anesthesia methods in patients who underwent endoscopic submucosal dissection for superficial esophageal carcinoma: A retrospective analysis in a single Japanese institution - Kuwata, Naoko Yagi; Gotoda, Takuji; Suzuki, Sho; Mukai, Shuntaro; Itoi, Takao; Moriyasu, Fuminori (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Despite being a valuable therapeutic option, it has not yet been reported whether endoscopic submucosal dissection (ESD) for superficial esophageal carcinoma should be performed under general or non-general anesthesia (sedation). Materials and Methods: The clinicopathological factors (age, sex, histology, tumor size, tumor location, tumor macroscopic morphology, and adverse events) of 110 superficial esophageal carcinoma lesions (98 patients) treated by ESD at a single Japanese institution from January 2007 to December 2013 were retrospectively reviewed using medical records. Results: Among 110 lesions, 94 lesions were resected under general anesthesia, and 16 lesions were resected under non-general anesthesia by an experienced endoscopist. Although the number of complications was 12 in the group of general anesthesia and 1 in sedated patients, no significant differences between both groups were found in the incidence of adverse events (total adverse events: 12.2% versus 1.02%, p=0.456; mediastinal emphysema: 11.2% versus 1.02%, p=0.518; pulmonary atelectasis: 1.02% versus 0%, p=0.679). All of the events could be managed conservatively. Conclusion: For ordered management of accidental events during esophageal ESD, general anesthesia might be a crucial option for a better clinical outcome even when administered by non-experienced operators.